Efficacy of Biofilm Removal on the Dental Implant Surface by Sodium Bicarbonate and Erythritol Powder Airflow System - Pujarern, Patr; Klaophimai, Arthit; Amornsettachai, Parinya; Panyayong, Woraphong; Chuenjitkuntaworn, Boontharika; Rokaya, Dinesh; Suphangul, Suphachai (European Journal of Dentistry, 2024)
Objective Peri-implantitis is a common complication in implant therapy and it is one of the main contributing factors to implant failure. This can be prevented by regular maintenance with mechanical debridement. One of the recent mechanical debridement methods is air abrasion therapy using different abrasive powders. This study aimed to evaluate the two common abrasive powders of different sizes (sodium bicarbonate and erythritol) for their biofilm cleaning efficacy on dental implant surfaces.Materials and Methods In an in vitro setting, a total of 33 implants were divided into three groups: Group 1 (n =11) = no treatment; group 2 (n = 11) = air abrasion therapy treated group using a sodium bicarbonate powder (AIRFLOW Powder Classic Comfort, EMS Electro Medical Systems, Nyon, Switzerland); and group 3 (n = 11) = air abrasion therapy treated group using an erythritol powder (AIRFLOW Powder Plus, EMS Electro Medical Systems, Nyon, Switzerland). The implants in each group were subjected to biofilm formation, and group 2 and group 3 were treated with air abrasion therapy of two different powders having different sizes with the same settings. The particle sizes were sodium bicarbonate (40 µm) and erythritol (14µm). The surface characteristics of the dental implants in three groups were studied from a digital camera and under the scanning electron microscope at different magnifications. The comparison of biofilm-removal efficacy between the three groups was performed by using a one-way analysis of variance with post-hoc Dunnett's T3 test. A p-value less than 0.05 was chosen to indicate statistical significance.Results There were no statistical differences (p > 0.05) between the two powder-treated groups for the biofilm cleaning efficacy. However, both groups showed significantly better biofilm-cleaning efficacy than the control group (p < 0.05).Conclusion This suggests that both powders are effective in removing biofilm from the implant surface under ideal conditions. However, there was no clear distinction between the cleaning potential of the two powders, as both performed in a similar manner.
Keywords: dental implants; peri-implantitis; mechanical debridement; air abrasion therapy; erythritol; sodium bicarbonate; biofilm removal